Use of 3D laser scanning for monitoring the dimensional stability of a Byzantine ivory panel. (August 2015) - Hess, Mona; Korenberg, Capucine; Ward, Clare; Robson, Stuart; Entwistle, Chris
Abstract : The British Museum has in its collections a magnificent Byzantine ivory panel. However, the panel has become warped over time and there is a join on the left side, where it has suffered a break in the past. It has been connected with two metal pins and adhesive in a previous conservation treatment but there is now concern that these could be having an adverse influence on natural movements within the ivory. Given the importance of the panel, the decision was made to leave the pins in place and monitor the stability of the panel. As the geometry of the panel is complex, it was felt that microscopic imaging would not be suitable and 3D laser scanning was used instead. This engineering metrology technique is increasingly used in cultural heritage and conservation to record minute three-dimensional changes with high spatial accuracy. The resulting dataset is a detailed metric 3D record of the object surface in-the-round and comparison of subsequent scans with a reference scan can indicate dimensional changes. As part of a monitoring campaign, the ivory panel was first scanned in January 2012 to provide a reference scan. It was then scanned again in autumn 2012 (no significant movement was detected) and will be scanned at regular intervals in the future. This case study demonstrates the potential of 3D laser scanning to monitor the dimensional stability of complex artefacts.